Acyclic Diene Metathesis (ADMET) Polymerization of 2, 2, 6, 6‐Tetramethylpiperidine‐1‐sulfanyl (TEMPS) Dimers. Issue 10 (24th May 2021) - Hobich, Jan; Huber, Birgit; Theato, Patrick; Mutlu, Hatice
Abstract : Inside Cover : Marrying acyclic diene metathesis polymerization and BiTEMPS chemistry offers a simple method to prepare a tailor‐made polymer with precise control over the primary structure. Pivotally, the macromolecule, decorated with sulfur‐nitrogen bonds in each repeating unit, exhibits light‐responsive reversible homolytic dissociation of disulfide linkage, where the specific treatment (e.g., anaerobic condition) is not required. The latter allows reorganization of the polymeric architecture on exposure to the stimulus, and this molecular‐based response is foreseen to be translated to the macroscopic scale. This work is found in article number 2100118 by Hatice Mutlu and co‐workers.